A Case Study on Parasitic Infectious Diseases in Pregnant Women in Four Hospitals in Ghana. - Achoribo, V. (University of Ghana, 2004)
The prevalence o f parasitic infectious disease among pregnant women in some communities within rural and urban settlements in Ghana was investigated. The study was conducted in Adabraka and Mamobi Polyclinics in the Greater Accra Region, Nsawam and St. Martin’s Hospital in the Eastern Region. The aim o f this study was to compare incidence o f parasitic diseases in pregnant women, and to find out how these infections axe related to the age o f expectant mothers from these hospitals, also whether there had been an increase or decrease in the incidence o f these parasitic diseases over the past few years. Parasitological examinations "were carried out on blood urine and stool samples from pregnant women within ages 11-45 years. These samples were collected from 98, 515, 280 and 400 women from Adabraka, Mamobi Polyclinics, St. Martin’s and Nsawam Hospitals respectively. Results show that many pregnant women within ages 1 6 - 2 5 years were positive for parasitic infections. Intestinal flagellates infestation was high at Adabraka (90%), Mamobi (77%), and Ascaris infestation (87%) at Nsawam Hospital. Candidiasis and Trichomonas vaginalis infections were also high (80% and 20% respectively). Malaria infection was significantly higher at Mamobi Polyclinic (64%), followed by St. Martins Hospital (55%), and Adabraka Polyclinic (27%). Incidence of parasitic diseases also decreased slightly over the years whilst T. vaginalis and Candidiasis infections increased for ages 16-25. This evidence shows that parasitic diseases may be a public health problem and effective control measures must be employed to control it. Improvements in water supply, sewerage disposal and general environmental hygiene through human behavioural changes and health education may be used
Theses (Mphil)